2018
DOI: 10.1136/bmjdrc-2017-000460
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient diabetes management by specialized diabetes team versus primary service team in non-critical care units: impact on 30-day readmission rate and hospital cost

Abstract: ObjectiveWe compared the cost-effectiveness of two inpatient diabetes care models: one offered by a specialized diabetes team (SDT) versus a primary service team (PST).Research design and methodsWe retrospectively evaluated 756 hospital admissions of patients with diabetes to non-critical care units over 6 months. Out of 392 patients who met the eligibility criteria, 262 were matched 1:1 based on the mean of the initial four blood glucose (BG) values after admission. Primary outcomes were 30-day readmission ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 18 publications
6
57
0
Order By: Relevance
“…The impact of diabetes inpatient teams on readmission rates has been evaluated in studies, with differing outcomes reported . One such study found reduced 30‐day readmissions in people admitted to medical services, while readmissions to surgical services increased ; in the present study, only a relatively small proportion of the inpatients with diabetes was included in the intervention, in contrast to the present study, which impacted the whole diabetes inpatient population and additionally factored in the changes in the length of stay and readmissions of those without diabetes into the analyses.…”
Section: Discussionmentioning
confidence: 68%
“…The impact of diabetes inpatient teams on readmission rates has been evaluated in studies, with differing outcomes reported . One such study found reduced 30‐day readmissions in people admitted to medical services, while readmissions to surgical services increased ; in the present study, only a relatively small proportion of the inpatients with diabetes was included in the intervention, in contrast to the present study, which impacted the whole diabetes inpatient population and additionally factored in the changes in the length of stay and readmissions of those without diabetes into the analyses.…”
Section: Discussionmentioning
confidence: 68%
“…4) Others using teams of caregivers have achieved a reduction in 30-day all-cause readmissions of 30 percent. [14] In our diabetic patients with Grand-Aides, hospital readmissions were significantly reduced by 50 percent.…”
Section: Discussionmentioning
confidence: 70%
“…This could be explained by a number of reasons: primarily, the interventions that a DISN is able to provide, as well as the outpatient follow‐up and telephone contact provided by DISNs after discharge, prevented the need for further hospitalisation. Studies have shown that patient education performed by a specialised team, specifically diabetes specialist nurses, decreases readmission rates by improving patient adherence to treatment and improving glycaemic control, even after the patient has been discharged . Improved self‐management can make the transition after discharge easier for patients and improve the chances of a normal recovery without the need for further hospital intervention .…”
Section: Discussionmentioning
confidence: 99%
“…Interventions provided by DISNs typically include monitoring blood glucose, managing medication and providing support and advice to both the patient and the primary care team, with a strong emphasis on education . Point‐of‐care testing (POCT) is used by DISNs to enable clinical decisions to be made at the time of assessment, allowing fast diagnosis, monitoring and treatment . Studies have reported that POCT is associated with improved patient satisfaction and better glycaemic control .…”
Section: Introductionmentioning
confidence: 99%